2019
DOI: 10.1097/rlu.0000000000002541
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse-Type Tenosynovial Giant Cell Tumor of the Thoracic Spine

Abstract: D-TGCT (diffuse-type tenosynovial giant cell tumor) is a benign proliferative disorder of the synovial membranes that usually occurs in the appendicular skeleton, especially large joints such as the knee, hip, and elbow. It rarely involves the spine. In this report, we describe a rare case of D-TGCT in the thoracic spine, which showed a lytic lesion with high FDG uptake. It can mimic metastases or neurogenic tumors and should be included in the differential diagnosis of spinal tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 11 publications
1
8
0
Order By: Relevance
“…In the present study, GCTTSs showed moderate to marked enhancement, probably due to the proliferative capillaries within the collagenous stroma within the lesion [10]. 18 F-FDG PET/CT imaging of spinal GCTTS has been infrequently reported [11][12][13][14]. In previous studies, GCTTS showed a high 18 F-FDG uptake [11][12][13][14].…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…In the present study, GCTTSs showed moderate to marked enhancement, probably due to the proliferative capillaries within the collagenous stroma within the lesion [10]. 18 F-FDG PET/CT imaging of spinal GCTTS has been infrequently reported [11][12][13][14]. In previous studies, GCTTS showed a high 18 F-FDG uptake [11][12][13][14].…”
Section: Discussionsupporting
confidence: 57%
“…18 F-FDG PET/CT imaging of spinal GCTTS has been infrequently reported [ 11 14 ]. In previous studies, GCTTS showed a high 18 F-FDG uptake [ 11 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…G iant cell tumor of the tendon sheath (GCTTS) is a slowly progressive neoplasm originating from the synovial cells in the bursa, tendon sheath, and joints, which highly impacts the quality of life. [1][2][3][4] This neoplasm rarely occurs in the spine, and only about 85 spinal cases have been reported in the past few decades. 4,5 Surgical management has been adopted as a conventional method for treating spinal GCTTS.…”
mentioning
confidence: 99%
“…2 Several case reports and small series have shown that tenosynovial giant cell tumor can show increased FDG uptake and may cause false-positive result on FDG PET/CT. [6][7][8][9][10] FDG PET/CT findings of facet joints have been rarely reported before. This case indicates tenosynovial giant cell tumor, although rare, should be included in the differential diagnosis of abnormal facet joint FDG accumulation.…”
mentioning
confidence: 99%